Select Teaching: authoring tool for building Learning Objects for language teachers´ training and teaching support - Medola, Larissa da Silva; Gomes, Celina de Oliveira Barbosa; Felippsen, Eduardo Alberto (Revista Liberato, 2020)
The use of technological instruments in educational environments and contexts was facilitated by the popularization of technology in general, which significantly supported the teaching-learning process. This fact highlights the importance of teachers´ training to use these tools, as well as the presence of softwares and other appropriate tools for specific educational approaches. Thus, the present paper presents the creation of a didactic tool, the "Select Teaching", to be applied in the production of didactic material in the format of electronic handouts with foreign language content. The research is mainly characterized by the feasibility of considering these handouts as Learning Objects to be used by the language teachers of the Federal Institute of Paraná (IFPR) - Campus Assis Chateaubriand.